Clinical Practice Guidelines for Ventilation Associated Pneumonia. - Marcos Diosdado Iraola Ferrer.; Belkys Rodríguez Llerena.; Héctor Cruz de los Santos.; Eddy Pereira Valdés. (Medisur)
Clinical Practice Guidelines for Ventilation Associated Pneumonia. Conceptualized as the bacterial pneumonia that develops in patients receiving mechanical ventilation for more than 48 hours, which is not present at the beginning of the ventilation. We review the concept, prevention and treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.